2022
DOI: 10.1021/acsomega.2c05760
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Synthesis of Nanosilica from Silica Sand for Plant Stimulant Applications

Abstract: Nanosilica is a versatile nanomaterial suitable as, e.g., drug carriers in medicine, fillers in polymers, and fertilizer/pesticide carriers and potentially a bioavailable source of silicon in agriculture. The enhanced biological activity of nanosilica over quartz sand has been noted before; it is directly related to the altered physicochemical properties of the nanoparticles compared to those of the bulk material. Therefore, it is feasible to use nanosilica as a form of plant stimulant. Nanosilica synthesis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The broad wide peak and the absence of any sharp diffraction peak confirm the amorphous nature of the extracted silica [ 21 ]. Moreover, the broad peak width reveals the nanometer-sized silica particle size [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The broad wide peak and the absence of any sharp diffraction peak confirm the amorphous nature of the extracted silica [ 21 ]. Moreover, the broad peak width reveals the nanometer-sized silica particle size [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bamboo leaf silica has the potential to increase the height of red beet plants, so the dose needs to be increased considering the importance of silica for plant growth. Silica fertilization can increase plant height growth, silica increases the efficiency of photosynthesis and nutrient absorption in the soil (Fitriani & Haryanti, 2016;Putri et al, 2017;Hoang et al, 2022). Providing 7.5 ml/L nano silica fertilizer increased the height of black rice plants by Putri et al, (2017).…”
Section: Plant Height (Cm)mentioning
confidence: 99%
“…Applications 2.5 ml/L nano silica fertilizer increases the height of tomato plants (Fitriani & Haryanti, 2016). Meanwhile, research results from Hoang et al, (2022) reported that spraying 6.7 mg/L nano silica fertilizer twice spraying could increase the height of corn plants. Fertilizing via leaves and roots as one of the agricultural intensification efforts is an effort that aims to increase the supply of nutrients needed by plants to increase production and quality of crops.…”
Section: Plant Height (Cm)mentioning
confidence: 99%
“…Recently, the sol-gel methods have been reported potential for industrial-scale manufacturing of SiNPs from silica sands ( Fig. 4 B) [ 56 ]. The size range of SiNPs was obtained from 16 to 37 nm with high purity and their evaluation in maize plants showed a significant enhancement of plant growth in terms of blase height and plant height.…”
Section: Nano-fertilizers (Nfs)mentioning
confidence: 99%
“…Reprinted from Ref. [ 56 ], Copyright 2022 ACS. (C) SiNPs stimulate the immunity of rice plants to resistance to biotic and abiotic stress.…”
Section: Nano-fertilizers (Nfs)mentioning
confidence: 99%